Standardising the preanalytical reporting of biospecimens to improve reproducibility in extracellular vesicle research – A GEIVEX study. Issue 4 (31st March 2023) - López‐Guerrero, José A.; Valés‐Gómez, Mar; Borrás, Francesc E.; Falcón‐Pérez, Juan Manuel; Vicent, María J.; Yáñez‐Mó, María
Abstract: The standardization of clinical studies using extracellular vesicles (EVs) has mainly focused on the procedures employed for their isolation and characterization; however, preanalytical aspects of sample collection, handling and storage also significantly impact the reproducibility of results. We conducted an online survey based on SPREC (Standard PREanalytical Code) among members of GEIVEX (Grupo Español de Investigación en Vesiculas Extracelulares) to explore how different laboratories handled fluid biospecimens destined for EV analyses. We received 70 surveys from forty‐three different laboratories: 44% focused on plasma, 9% on serum and 16% on urine. The survey indicated that variability in preanalytical approaches reaches 94%. Moreover, in some cases, researchers had no access to all relevant preanalytical details of samples, with some sample aspects with potential impact on EV isolation/characterisation not coded within the current version of SPREC. Our study highlights the importance of working with common standard operating procedures (SOP) to control preanalytical conditions. The application of SPREC represents a suitable approach to codify and register preanalytical conditions. Integrating SPREC into the SOPs of laboratories/biobanks will provide a valuable source of information and constitute an advance for EV research by improving reproducibility and credibility.